Analysis of Instagram Social Media Management in @Hutanpinuslimpakuwuss Account on the Development of Limpakuwus Forest Tourism Object - Nurandini, Syifa; Agus Triyono (Jogjakarta Communication Conference (JCC), 2024)
The use of Instagram social media has increased to the private level, such as Nature Tourism which has visitors with the characteristics of finding out all Nature Tourism information through Instagram. Therefore, it is necessary to manage social media content to become a means of communication between the company and its audience. This research uses interactive analysis of Miles and Huberman. The theory used is The Circular Model of Some by Regina Luttrell in her book Social Media How to Engage, Share, and Connect. This research method is descriptive with a qualitative approach. Data collection techniques are observation and interviews with key informants, namely the management team of tourism social media and the informant is the head of the social media management team. This research uses source triangulation for data validity techniques. The results show that managing Instagram content starts with understanding the purpose of using social media and addressing issues on content posted by tourism. The optimize aspect includes time, content analysis, and understanding of Instagram branding strategies. The management aspect is done by creating a posting schedule, and management control is used to assess and be responsible for the management of the company. In the engage aspect, establishing a good relationship with the online community (followers) to get Instagram exposure on the content created.